Efficient management of insecure fossil fuel Imports through taxing (!) domestic green energy? - Thomas Eichner; Rüdiger Pethig (Center for Economic Studies and ifo Institute (CESifo), 2010)
A small open economy produces a consumer good, green and black energy, and imports fossil fuel at an uncertain price. Unregulated competitive markets are shown to be inefficient. The implied market failures are due to the agents' attitudes toward risk, to risk shifting and the uniform price for both types of energy. Under the plausible assumptions that consumers are prudent and at least as risk averse as the producers of black energy, the risk can be efficiently managed by taxing emissions and green energy. The need to tax (!) green energy contradicts the widespread view that subsidization of green energy is an appropriate means to enhance energy security in countries depending on risky fossil fuel imports.
Keywords: F18; Q42; Q48; 330; price uncertainty; black energy; green energy; fossil fuel; Energiesteuer; Regenerative Energie; Fossiler Energieträger; Rohstoffpreis; Außenhandelspreis; Risikoaversion; Kleines-offenes-Land; Umweltökonomik; Theorie